PENTINGNYA MENGAWASI KAMPANYE DIGITAL - Rahmatunnisa, Mudiyati (Jurnal Keadilan Pemilu, 2022)
Advances in information and communication technology (ICT) have brought about signicant changes in the conduct of electoral campaigns. The campaign has incorporated online elements with the potential to reach a wider range of constituents and in a very fast time. However, at the same time, the use of digital campaigns also brings with it negative practices which ultimately threaten the integrity of the campaigns. This paper discusses a number of factors that underlie the importance of monitoring digital campaign activities which have now become a strategic alternative for election contestants in order to gain votes. This paper also discusses how digital campaign oversight can be carried out effectively. This study uses qualitative research method with literature studies to discuss in depth various rationales regarding the importance of digital campaigns to be monitored and effective forms of oversight to be able to realize fair and equal campaigns as an important basis for democratic elections. The study of literature is used as the data collection technique. Oversight of digital campaigns is very strategic because of a number of potential negative effects of manipulative practices that threaten the fundamental aspects of democratic campaigns, namely the right of voters to obtain valid and reliable information, as well as an equal level of playing eld for all election contestants. To realize these fundamental aspects, oversight of digital campaigns requires a conducive legal framework, supportive legislative institutions, capable monitoring and supervisory bodies, political parties that adhere to campaign norms and ethics, and constructive cooperation with social media platform owners. Keywords: Campaign,